Submersible touchless interactivity in conformable textiles enabled by highly selective overbraided magnetoresistive sensors - Pasindu Lugoda; Eduardo Sergio Oliveros-Mata; Kalana Marasinghe; Rahul Bhaumik; Niccolò Pretto; Carlos Oliveira; Tilak Dias; Theodore Hughes-Riley; Michael Haller; Niko Münzenrieder; Denys Makarov (Communications Engineering)
Abstract Miniature electronics positioned within textile braids leverages the persistent flexibility and comfort of textiles constructed from electronics with 1D form factors. Here, we developed touchless interactivity within textiles using 1D overbraided magnetic field sensors. Our integration strategy minimally impacts the performance of flexible giant magnetoresistive sensors, yielding machine-washable sensors that maintain conformability when integrated in traditional fabrics. These overbraided magnetoresistive sensors exhibit a detectivity down to 380 nT and a nearly isotropic magnetoresistance amplitude response, facilitating intuitive touchless interaction. The interactivity is possible even in humid environments, including underwater, opening reliable activation in day-to-day and specialized applications. To showcase capabilities of overbraided magnetoresistive sensors, we demonstrate a functional armband for navigation control in virtual reality environments and a self-monitoring safety helmet strap. This approach bridges the integration gap between on-skin and rigid magnetic interfaces, paving the way for highly reliable, comfortable, interactive textiles across entertainment, safety, and sportswear.